MODELAGEM E COMPARAÇÃO DE EFEITOS SIMULTÂNEOS DA FORMA URBANA SOBRE A GERAÇÃO DE ENERGIA FOTOVOLTAICA E O CONFORTO DOS ESPAÇOS EXTERNOS. O CASO DO BELENZINHO, EM SÃO PAULO - Marins, Karin; Girotti, Carolina; Pacifici, Martina; Cruz, Rafael (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The urban form is a complex structure, whose combination of elements demands multicriteria assessment, in order to achieve an overall improved performance. The objective is to analyze and discuss the performance of urban planning parameters, applied to the neighborhood of Belenzinho, in São Paulo, with regard to photovoltaic energy generation and environmental comfort of external spaces. The studied area is part of an urban zone under densification and transformation. Two simulations were carried out using Rhinoceros, associated with the Grasshopper and Diva plug-ins (photovoltaic energy assessment) and field climate collections associated with the Rayman application, as well as using Rhinoceros, for external space comfort assessment. The combined results of the simulations indicate that there is a certain intermediate range of verticality and built up density, which may result, in one hand, in certain losses in photovoltaic generation. However, on the other hand the intermediate results would allow regulating, better environmental comfort conditions for external urban spaces as well as inside of buildings.